PENGARUH CORPORATE GOVERNANCE, KARAKTER EKSEKUTIF, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) (Studi Pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2012-2016) - Eka, Lestari fitri Mardiana; Zirman, Zirman; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of corporate governance, excecutivecharacters, firm size, and leverage on the extent of tax avoidance with proxy book taxgap. The population in this study is the Registered Minning companies in IndonesiaStock Exchange in 2012 until 2016. The sample was determined by the purposivesampling method and obtain 30 companies. Type of data used was secondary dataobtained from www.idx.co.id or corporate websites. The method of analysis used ismultiple regression analysis. The results of study show that institusional ownership hassignificant effect on tax avoidance, where the significant value are 0,026<0,05. Qualityauditte has significant effect on tax avoidance, where the significant value are0,028<0,05.Independent commisaries has a significant effect on tax avoidance, where thesignificant value are 0,121>0,05. Audit commite has no significant effect on taxavoidance, where the significant value are 0,021<0,05. Exchecutive charachters hassignifikan effect on tax avoidance, where the significant value are 0,512>0,05. Firm sizehas significant effect on tax avoidance, where the significant value are 0,040<0,05.Leverage has no significant effect on tax avoidance, where the significant value are0,036<0,05.Keywords : corporate governance, exchecutive charachters, firm size, leverage, and taxavoidance.